Desenvolvimento de mudas de Moringa oleifera Lam. em diferentes substratos - (:unkn) unknown (Universidade Federal do Oeste do Pará, 2019)
The objective of this study was to evaluate the initial development of Moringa oleifera Lam 20 seedlings from the use of different substrates. The seedlings were produced in a polyethylene bag, used for 21 the composition of the treatments cattle manure, chicken litter, coconut fiber, carbonized rice straw and 22 black earth. The experiment was conducted in a completely randomized design consisting of 8 treatments 23 and 13 repetitions. At 60 days after sowing, plant height, neck diameter, shoot and root mass, and Dickson 24 quality index (IQD) were evaluated. By analyzing the data together, we found the best seedling growth 25 variables in the combination of 20% chicken litter and 10% cattle manure. Thus, there is a tendency of 26 dominance by the T7 and T4 treatments in the evaluated variables. Seedlings produced with substrates 27 formulated with chicken manure 20% and bovine manure 10%, in the substrate composition showed gains 28 in the evaluated variables and may be a viable alternative for the production of moringa seedlings.
Keywords: esterco bovino; esterco de frango; adubação orgânica; mudas florestais; CNPQ:: CIÊNCIAS AGRÁRIAS